Characteristics and respiratory risk profile of children aged less than 5 years presenting to an urban, Aboriginal‐friendly, comprehensive primary health practice in Australia. (24th April 2017) - Hall, Kerry K; Chang, Anne B; Anderson, Jennie; Dunbar, Melissa; Arnold, Daniel; O'Grady, Kerry‐Ann F
Abstract : Aim: There are no published data on factors impacting on acute respiratory illness (ARI) among urban Indigenous children. We describe the characteristics and respiratory risk profile of young urban Indigenous children attending an Aboriginal‐friendly primary health‐care practice. Methods: We conducted a cross‐sectional analysis of data collected at baseline in a cohort study investigating ARI in urban Indigenous children aged less than 5 years registered with an Aboriginal primary health‐care service. Descriptive analyses of epidemiological, clinical, environmental and cultural factors were performed. Logistic regression was undertaken to examine associations between child characteristics and the presence of ARI at baseline. Results: Between February 2013 and October 2015, 180 Indigenous children were enrolled; the median age was 18.4 months (7.7–35), 51% were male. A total of 40 (22%) children presented for a cough‐related illness; however, ARI was identified in 33% of all children at the time of enrolment. A total of 72% of children were exposed to environmental tobacco smoke. ARI at baseline was associated with low birthweight (adjusted odds ratio (aOR) 2.54, 95% confidence interval (CI) 1.08–5.94), a history of eczema (aOR 2.67, 95% CI 1.00–7.15) and either having a family member from the Stolen Generation (aOR 3.47, 95% CI 1.33–9.03) or not knowing this family history (aOR 3.35, 95% CI 1.21–9.26). Conclusions: We identified an urban community of children of high socio‐economic disadvantage and who have excessive exposure to environmental tobacco smoke. Connection to the Stolen Generation or not knowing the family history may be directly impacting on child health in this community. Further research is needed to understand the relationship between cultural factors and ARI.